Evaluation and analysis of incidence and risk factors of lower extremity venous thrombosis after urologic surgeries: A prospective two-center cohort study using LASSO-logistic regression. (May 2021) - Tang, Guyu; Qi, Lin; Sun, Zepeng; Liu, Jing; Lv, Zhengtong; Chen, Lingxiao; Huang, Bin; Zhu, Shuai; Liu, Yao; Li, Yuan
Abstract: Background: Deep vein thrombosis (DVT) is among the most frequent complications of surgery. This study aimed to analyse the incidence and risk factors of lower extremity venous thrombosis after urologic surgery. Materials and methods: This prospective two-centre study was conducted from August 2019 to January 2020. Patients who underwent urological procedures were enrolled. The primary endpoint was the detection of asymptomatic or symptomatic DVT of the lower extremity within 7 days after surgery. Univariate and least absolute shrinkage and selection operator (LASSO) logistic regression analyses were performed. Results: Fifty-six of 1011 patients developed DVT. In the univariate analysis, Barthel Index ≤40, d -dimer level ≥0.5 mg/L and age ≥60 years (p < 0.001) were identified as the most significant risk factors. The LASSO logistic regression model identified nine factors: age, history of DVT, lymph node dissection, perioperative steroid use, Caprini score, Barthel Index, D-dimer level, cystectomy, and prostatectomy. Conclusion: Our study used the LASSO logistic regression model to provide reliable data on the risk factors for DVT after comprehensive urologic surgery. The incidence of DVT in this group was 5.54%. This might facilitate individualised anticoagulant management in patients undergoing urological procedures. Highlights: This study analysed the risk factors and incidence of deep vein thrombosis (DVT). A newly regression model was constructed to evaluate risk factors. D-dimer level, Barthel Index and Caprini score are significant risk factors for DVT. Surgeons should pay attention to DVT in cancer and non-cancer urologic surgeries.